2017
DOI: 10.1016/j.scr.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

CD146 (MCAM) in human cs-DLK1−/cs-CD34+ adipose stromal/progenitor cells

Abstract: To precisely characterize CD146 in adipose stromal/progenitor cells (ASCs) we sorted the stromal vascular faction (SVF) of human abdominal subcutaneous white adipose tissue (sWAT) according to cell surface (cs) expression of CD146, DLK1 and CD34. This test identified three main SVF cell populations: ~50% cs-DLK1/cs-CD34/cs-CD146 ASCs, ~7.5% cs-DLK1/cs-CD34/cs-CD146 and ~7.5% cs-DLK1/cs-CD34/cs-CD146 cells. All cells contained intracellular CD146. Whole mount fluorescent IHC staining of small vessels detected C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Later, it was also recognized as a marker for pericytes 24, 26, which have been identified as the natural ancestors of MSCs 27, 28. In human tissues, CD146 + cell was regarded as the mural cells of blood micro vessels 29, 30. Previous reports also showed that CD146 was associated with cell migration and self-renewal 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…Later, it was also recognized as a marker for pericytes 24, 26, which have been identified as the natural ancestors of MSCs 27, 28. In human tissues, CD146 + cell was regarded as the mural cells of blood micro vessels 29, 30. Previous reports also showed that CD146 was associated with cell migration and self-renewal 31, 32.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it is intriguing that a subset of these cells exhibiting the CD31−CD34+CD146− profile, previously found to identify a stem cell lineage [25,64,65], also grew proportionally to the culture period. In addition, possibly important ramifications may reveal that some antigens that have been ambiguously associated with stemness, including CD200, CD248, and CD271 [66,67], were reinforced during the culture, while all subsets featuring CD146, which has previously been recognized as a surrogate for stemness [40,[68][69][70][71] were sequestered. Concerning interpersonal variability, the spread of the data roughly follows previously reported trends [49,72], except for two specific subsets, the CD166+CD271−CD248+ and CD166+CD271+CD248+, which were identified only in a single donor.…”
Section: Discussionmentioning
confidence: 99%
“…ASCs were isolated and maintained as previously described [23]. Briefly, sWAT samples were handled under sterile conditions, washed twice with PBS and dissected.…”
Section: Isolation and Culture Of Human Adipogenic Stem/ Progenitor Cmentioning
confidence: 99%